Modulation of Emotional Conflict Processing by High-Definition Transcranial Direct Current Stimulation (HD-TDCS) - Kuehne, Maria; Schmidt, Katarina; Heinze, Hans-Jochen; Zaehle, Tino (Frontiers in Behavioral Neuroscience, 2019)
Cognitive control is characterized by selective attention to relevant stimuli while irrelevant, distracting stimuli are inhibited. While the classical color-word Stroop task was implemented to investigate the processes of cognitive control, a variant of it—the face-word Stroop task—allows for directly investigating processes of emotional conflict control. It is thought that the prefrontal cortex (PFC) is especially involved in processes of cognitive control, while the rostral cingulate is mainly associated with the resolution of emotional conflict. In recent years, the role of the dorsolateral PFC (DLPFC) during the performance of the classical Stroop was investigated by means of transcranial direct current stimulation (tDCS) with divergent results. However, investigations to the causal role of the DLPFC during emotional conflict processing are rare. For this purpose, we used a combined high-definition tDCS (HD-tDCS)/electroencephalogram (EEG) setting to investigate the impact of anodal stimulation of the left DLPFC on behavioral and electrophysiological responses during an emotional face-word Stroop task. In two separate sessions, participants (n = 18) received either sham or anodal HD-tdc stimulation while responding to the emotional expression of the face and ignoring the word. Our results show that anodal stimulation of the left DLPFC increases the behavioral interference effect, that is, the already decelerated reaction times (RTs) to incongruent trials further increase while RTs to congruent trials remain largely unaffected. Furthermore, the stimulation modulates brain response to emotional facial expressions during the face-word Stroop generally—independent of the valence of the emotional expression and the congruency of the combined face-word presentation, the N170 decreases during anodal stimulation. These results reveal that the left DLPFC has a causal role in emotional conflict processing during a face-word Stroop.